Eficácia de Inseticidas para o Manejo de Diaphorina citri Kuwayama (Hemiptera: Psyllidae) em Citros - Yamamoto, Pedro T.; Fellipe, Marcos R.; Sanches, André L.; Coelho, Juliana H. C.; Garbim, Luiz F.; Ximenes, Nivian L. (BioAssay, 2009)
The purpose of this research was to evaluate the efficiency of systemic and spray insecticides to control Diaphorina citri in citrus orchard. The experiments was carried out in the Marchesan Farm, located in the municipality of Matão, SP, in Valencia sweet orange on Rangpur lime orchard. The evaluations were consisted in the counting of adults present on the plant canopy, walking around the canopy, and observation of four new branches/plant, taken randomly in the periphery of the Valencia sweet orange canopy for nymphs, considering the absence or presence. In spray, the insecticides thiamethoxam, imidacloprid, acetamiprid, lambda-cyhalothrin, deltamethrin, fenpropathrin, methidathion, dimethoate, ethion, thiamethoxam + lambda-cyhalothrin, abamectin and etofenproxi were efficient to control adults and nymphs of D. citri, and could be an option to reduce the vector population. In application in the soil, drench or injected, for thiamethoxam, aldicarb and imidacloprid, the control period for adults and nymphs were from 45 to 60 days in 2-year-old sweet orange.